Sustainable Tourism of Sawahlunto City as World Cultural Heritage Analysis (WBD) - ranny .; Siti Fatimah (The Tourism, Heritage and Recreation Sport Center, Universitas Negeri Padang, 2020)
The purpose of this research is to analyse and describe the implementation of sustainable tourism in the tourist area of Ombilin coal mine in Sawahlunto, after being designated as World HERITAGE by UNESCO Cultural category. The tourist area of Ombilin coal mine city of Sawahlunto as World Heritage, is said to be sustainable, when the aspects of sustainable tourism are carried out. Then it is said to be not sustainable, if there is an aspect in sustainable tourism there is not yet done. The research method used in this study is qualitative with a type of descriptive research. The selection technique of informant with purposive sampiling. Furthermore, the analysis of the data obtained that the tourism area of the Ombilin coal mine city Sawahlunto as the world heritage has not been sustainable. Judging from the aspects of sustainable tourism of the tourist areas Ombilin coal mine city of Sawahlunto has not fulfilled 100% of these three aspects, namely environmental, economic and socio-cultural aspects. Based on the results of the research, tourism in the tourist area Ombilin coal mine city of Sawahlunto as World Heritage can be said to be not sustainable. In addition, there needs to be synergity of government with the community and business people in the development of tourism to go to sustainable tourism.